1995
DOI: 10.1002/(sici)1097-4571(199501)46:1<52::aid-asi6>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactive thesaurus navigation: Intelligence rules OK?

Abstract: We discuss whether it is feasible to build intelligent ruleor weight-based algorithms into general-purpose software for interactive thesaurus navigation. We survey some approaches to the problem reported in the literature, particularly those involving the assignment of "link weights" in a thesaurus network, and point out some problems of both principle and practice. We then describe investigations which entailed logging the behavior of thesaurus users and testing the effect of thesaurus-based query enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 8 publications
4
38
0
2
Order By: Relevance
“…A thesaurus is an external expansion source in several studies on real users' searching. Jones et al (1995) tested query expansion with the INSPEC thesaurus in the INSPEC database with the best match system OKAPI. Genuine users with own information needs ran first their own query.…”
Section: Related Studiessupporting
confidence: 85%
See 1 more Smart Citation
“…A thesaurus is an external expansion source in several studies on real users' searching. Jones et al (1995) tested query expansion with the INSPEC thesaurus in the INSPEC database with the best match system OKAPI. Genuine users with own information needs ran first their own query.…”
Section: Related Studiessupporting
confidence: 85%
“…Based on results at document cut-off value (DCV) 20 no significant difference in the effectiveness of the original and the expanded queries was detected, whether run against full text or INSPEC index terms. The expansion had a reordering effect on the result sets, however (Jones et al, 1995). Sihvonen and Vakkari (2004) studied subject novices' and experts' query formulation and expansion.…”
Section: Related Studiesmentioning
confidence: 99%
“…The weightings may be based on criteria such as number of connections, number of co-occurrences, path length, and type of relationship [Jones 1995]. In [Voorhees 1994], for instance, the expanded query vector is comprised of subvectors of eleven different concept types with an associated importance weight: one for original query terms, one for synonyms, and one each for the other relation types contained within the noun portion of WordNet.…”
Section: Query Reformulationmentioning
confidence: 99%
“…Some studies have suggested that users who have reasonable understanding about the search topic are able to make use of thesaurus tools in the retrieval task of query formulations. For instance, users in academic environment found it informative and useful to use the INSPEC thesaurus navigation feature for query enhancement (Jones, Gatford, Robertson, Hancock-Beaulieu, Secker, & Walker, 1995). In a test of whether an enhanced thesaurus will be useful in a real work environment, Nielsen (2004) showed that domain experts perceived that a word association thesaurus was useful for query formulation.…”
Section: Domain Knowledgementioning
confidence: 99%